Efforts to Form Religious Character of MTs Al-Ghozali Grade VIII Students Through Learning Islamic Cultural History - Muhamad Aditiyah; Ahmad Khotibul Umam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Character is behavior, actions, human nature that is naturally fundamental in humans, currently experiencing a crisis that has a great influence on the world of education, namely a character crisis. Seeing this reality, character education needs to be given to this country. It is known that in Indonesia there are many different religions that understand each other and recognize the uniqueness of each religion, accept differences and respect tolerance including Islam, in Islamic teachings religious values, religious in Islam there are five things, namely aqidah, worship, charity, morals (ihsan) and knowledge. How can efforts to develop character and religion unite, both components are needed to change children's behavior for the better, for that it is necessary to make efforts to form a religious character in children intended to instill values ​​of goodness and exemplary morals so that they become habits when they are adults or at the next level of education. By using qualitative methods using observation analysis, and emotional approaches with the aim of obtaining information from students and providing motivation to students. So that students have a positive basic character.